The influence of Renaissance heritage on tourism of Northern Italy: Case study of Ferrara and Milan - Zlopaša, Jovana Marko; Solarević, Milica (Turizam, 2020)
In their turbulent history cities of Northern Italy experienced one of the most significant changes during the Renaissance period. The development of urbanism and the transformation of architectural style in the 15th and 16th centuries laid the foundations of modern cities of the Padua Valley. Construction and architecture were a visible manifestation of the power so the families of Northern Italy, Visconti and Sforza in Milan and Este in Ferrara, become patrons to many Renaissance artists wanting to show their supremacy over other city-states in humanistic manner. While today the renaissance core of Milan is only a small segment of modern Megapolis, Ferrara has not experienced significant changes in the spatial organization of urban area. Nevertheless, both cities base their tourist offer on castles, palaces, and other buildings from the renaissance period. This paper is trying to show just how the renaissance in urbanism and architecture had far-reaching effects on the modern tourism of these two centers of humanistic culture. The influence of Renaissance heritage is analyzed by descriptive and comparative method and SWOT analyses.